The molecular basis of phenylalanine hydroxylase deficiency in Croatia - Zschocke, Johannes; Preusse, Astrid; Sarnavka, Vladimir; Fumic, Ksenija; Mardešic, Duško; Hoffmann, Georg F.; Baric, Ivo (Human mutation, 2003)
We present the results of a comprehensive analysis of mutations, polymorphisms and haplotypes in the phenylalanine hydroxylase (PAH) gene in 39 Croatian families with phenylketonuria (PKU). A total of 21 disease-causing mutations was identified on 78 out of 79 independent chromosomes. The commonest mutation, R408W on haplotype 2 was found with a relative frequency of 37 %. P281L accounted for 11 %, R261Q and E390G each for 9 % of mutant chromosomes. There were three novel mutations: L249P (c.746T>C) in exon 7, IVS8+2T>C (c.912T>C) in intron 8, and F402L (c.1206T>G) in exon 12 of the PAH gene. Two known PKU mutations were found in cis on the same chromosome in one family, highlighting the need to perform full mutation scanning in recessive disease genes for molecular diagnosis even if two known mutations have been identified in a patient. This is the first comprehensive report on PKU mutations in southeastern Europe, adding to the growing bulk of molecular data for population genetic investigations. © 2003 Wiley-Liss, Inc.
Gesehen am 22.12.2020